Non-invasive electrical synchrony method to guide para-hisian stimulation implant technique. (25th November 2020) - Logarzo, E; Ortega, D; Barja, L; Paolucci, A; Mangani, N; Revollo, G; Aboy, J
Abstract: Introduction: Right ventricular apex stimulation solves electrical disorder but electrical disynchrony can be generated. Left bundle branch block results in heart failure and device upgrade is needed in some cases. Para-hisian stimulation generates a physiological cardiac activation through normal conduction system. Sheaths and special leads are used with current techniques. We developed an implantation technique guided by non-invasive electric synchrony using conventional screw-in leads. Synchromax is a novel device used to evaluate non-invasive cardiac electrical synchrony. It is easy to understand, fast to obtain, non-invasive and reproducible. Synchromax was analyzed in previous studies and correlated with other methods. Objective: Usefulness and safety of non-invasive cardiac electrical synchrony method using conventional screw-in leads to guide para-hisian device implantation. Materials and methods: 421 patients were evaluated. All patients had indication of ventricular stimulation (pacemaker and ICD). Non-invasive electrical synchrony was performed with Synchromax study during the device implantations in all patients. Synchrony index and curves were analyzed. Type 2 curve and index between 0, 1 and 0, 4 were considered synchronous. Type 8 curve and index more than 0.7 were considered dyssynchronous. Attempt numbers, thresholds, fluoroscopy time and dislodgments were analyzed. Results: Mean age 69 years (±8 years). 67, 9% males. 421 devices were implanted (334 pacemakes and 87 ICDs). Sick sinus syndrome was the main pacemaker aetiology and dilated cardiomyopathy was in patients with ICD. Conventional screw-in leads were used in all cases. An implant technique was designed. A J-shaped curve with a small perpendicular curve at the tip is performed in the stylet. On average 1, 9 attempts were made. Thresholds average 1, 2 mV. High thresholds in 4 patients with selective parahisian stimulation. 7 dislodgments was evidenced (1, 6%). Fluoroscopy time average 8, 4 min. Type 2 curve and index under 0, 4 was obtained in 94, 5% of cases. Conclusions: Para-hisian pacemaker implantation guided by Synchromax method using conventional screw-in leads is safe and useful achieving a physiological stimulation. Few attempts were needed with this new technique. Thresholds were similar to those used in conventional technique. Funding Acknowledgement: Type of funding source: None